SISTEM TRANSAKSI FOREX TRADING MENGGUNAKAN METAQUOTES LANGUAGE 4 - Uning Lestari; Henderi Henderi (CCIT Journal, 2012)
Now a lot of online businesses is on offer on the internet, particularly in the field of business Forex Online Trading. Lots of software that is used by traders for trading such as FX Clearing. FX Clearing is a software that is often used to trade forex traders in particular that uses a mini account. However, traders often have floating lost in trading it is because emotions are not controlled by the traders themselves. One solution to solve this problem so that traders do not always have floating lost is using Expert Advisors, Expert Advisors are applications that traders use to trade automatically without monitor price movements for 24 hours of the usual traders in general. Expert Advisors designed using the C programming language in the platform MetaQuotes Language4 (MQL4). So expect the use of Expert Advisors can facilitates for traders to trade without having to monitor price movements for 24 hours, and is expected to be the desired profit without having lost a very significant, because it has particularly Expert advisors to the ability of otomats trading, trading without emotion, and the nonstop 24 hour trading capabilities.